Socioeconomic status and cigarette expenditure among US households: results from 2010 to 2015 Consumer Expenditure Survey. Issue 6 (15th June 2018) - Siahpush, Mohammad; Farazi, Paraskevi A; Maloney, Shannon I; Dinkel, Danae; Nguyen, Minh N; Singh, Gopal K
Abstract : Objectives: To examine (1) the association between household socioeconomic status (SES) and whether a household spends money on cigarettes and (2) socioeconomic variations in proportion of total household expenditure spent on cigarettes among smoking households. Methods: We pooled data from six consecutive years, 2010–2015, of the Consumer Expenditure Interview Survey. The interviews involved a structured questionnaire about household income, demographics and expenditures including expenditure on cigarettes. Households that reported cigarette expenditure in the previous 3 months were distinguished as smoking households. SES indicators were household poverty status, education and occupation of the head of household. Logistic regression was used to assess the association of household smoking status with SES. Fractional logistic regression was used to assess the association of cigarette expenditure as a proportion of total household expenditure with SES. The analysis sample size was 39 218. Results: The probability of spending money on cigarettes was higher among lower SES households. Households in poverty compared with those above 300% of poverty threshold had 1.86 (95% CI 1.61 to 2.16), households headed by a person with less than high school education compared with those headed by a person with at least a bachelor's degree had 3.37 (95% CI 2.92 to 3.89) and households headed by a blue-collar work compared with those headed by a person in a managerial occupation had 1.45 (95% CI 1.26 to 1.66) higher odds of spending money on cigarettes. Similarly, the proportion of total household expenditure spent on cigarettes was higher among lower SES smoking households. Conclusion: Lower SES households are more likely to spend money on cigarettes and spend a larger proportion of their total expenditure on cigarettes. We recommend strategies effective in reducing smoking among low SES smokers.